Effectiveness of manual physical therapy and /or mandibular exercises in the treatment of the articular temporomandibular disorder - a systematic review (Research, Society and Development, 2020)
Objective: Evaluate the effectiveness of manual therapy and exercises for improving function and/or pain in patients diagnosed with temporomandibular joint dysfunction (TMD) through a systematic review of the literature. Methods: A systematic and manual electronic search of the data was performed in the following databases: MEDLINE-Pubmed, Cochrane Library, Web of Science and Scopus (until 2020). The following descriptors were used: "physiotherapy", "physiotherapy modalities", "physiotherapy specialty", "manual therapy", "massage", "exercise", "temporomandibular joint", "temporomandibular disorder", "temporomandibular joint", "disc "," Previous Disc Displacement "," Randomized Controlled Clinical Trial "," Controlled Clinical Trial "," Effectiveness "," Effect "and" Effectiveness ". As an inclusion, studies should present patients with joint pain diagnosed by the Diagnostic Criteria for Research on TMD (RDC / TMD) and manual therapy as an intervention. Results: Only 1 randomized controlled clinical trial was included in the inclusion criteria. Physical therapy manual exercises, despite promoting significant improvement in all studied variables, did not represent an additional positive effect in relation to the instruction and guidance given to patients with unrestricted articular disc displacement. Manual physical therapy and physical therapy exercises, despite while promoted a significant improvement in all the studied variables, did not represent an additional positive effect in relation to the instruction and orientation given to patients with joint disc displacement without reduction. Conclusions: Weak supporting evidence regarding the use of these approaches in patients with joint TMD was found, revealing the need to conduct new studies with methodologies well delineated and higher level of evidence.